Magnetite-Based Nanostructured Coatings Functionalized with Nigella sativa and Dicloxacillin for Improved Wound Dressings - Gabriela Dorcioman; Ariana Hudiță; Bianca Gălățeanu; Doina Craciun; Ionel Mercioniu; Ovidiu Cristian Oprea; Irina Neguț; Valentina Grumezescu; Alexandru Mihai Grumezescu; Lia Mara Dițu; Alina Maria Holban (MDPI AG, 2022)
In this study, we report the performance improvement of wound dressings by covering them with magnetite-based nanostructured coatings. The magnetite nanoparticles (Fe3O4 NPs) were functionalized with Nigella sativa (N. sativa) powder/essential oil and dicloxacillin and were synthesized as coatings by matrix assisted pulsed laser evaporation (MAPLE). The expected effects of this combination of materials are: (i) to reduce microbial contamination, and (ii) to promote rapid wound healing. The crystalline nature of core/shell Fe3O4 NPs and coatings was determined by X-ray diffraction (XRD). Differential Scanning Calorimetry (DSC) and Thermo Gravimetric Analysis (TGA) have been coupled to investigate the stability and thermal degradation of core/shell nanoparticle components. The coatings' morphology was examined by scanning electron microscopy (SEM). The distribution of chemical elements and functional groups in the resulting coatings was evidenced by Fourier transform infrared (FTIR) spectrometry. In order to simulate the interaction between wound dressings and epithelial tissues and to evaluate the drug release in time, the samples were immersed in simulated body fluid (SBF) and investigated after different durations of time. The antimicrobial effect was evaluated in planktonic (free-floating) and attached (biofilms) bacteria models. The biocompatibility and regenerative properties of the nanostructured coatings were evaluated in vitro, at cellular, biochemical, and the molecular level. The obtained results show that magnetite-based nanostructured coatings functionalized with N. sativa and dicloxacillin are biocompatible and show an enhanced antimicrobial effect against Gram positive and Gram negative opportunistic bacteria.